Preparation of Polystyrene-Polyolefin Multiblock Copolymers by Sequential Coordination and Anionic Polymerization - 김동현 (The Graduate School, Ajou University, 2017)
Block copolymers composed of polyolefins (PO) and polystyrene (PS) are attractive materials that are not synthesized directly from the olefin and styrene monomers. A strategy for construction of PS-b-PO-b-PS triblock units directly from the olefin and styrene monomers is disclosed herein. PO chains (ethylene/1-octene or ethylene/1-pentene copolymers) were grown from dialkylzinc species bearing the -methylstyrene moiety (i.e., [4-(isopropenyl)benzyl]2Zn) by the so-called 'coordinative chain transfer polymerization (CCTP)' using a standard ansa-metallocene catalyst, rac-[Me2Si(2-methylindenyl)2]ZrCl2, activated with modified-methylaluminoxane (MMAO). Afterward, PS chains were grown from the Zn-alkyl sites and from the -methylstyrene moieties of the resulting PO chains by switching to anionic polymerization. When nBuLi(tmeda)2 was fed into the system as an initiator in a quantity fulfilling the criterion [Li] > [Zn] + [Al in MMAO], nBuLi(tmeda)2 successfully attacked the -methylstyrene moieties to generate the desired PS-b-PO-b-PS triblock units. However, in model studies, the attack of nBuLi(tmeda)2 on -methylstyrene in the presence of (hexyl)2Zn consumed two molecules of -methylstyrene per nBuLi to afford mainly R-CH2C(Ph)(Me)-CH2C(Ph)(Me)Li, where R is either an n-butyl or hexyl group originating from nBuLi or (hexyl)2Zn, respectively. This observation suggests that the block copolymer does not simply comprise the PS-b-PO-b-PS triblock, but instead comprise a multiblock containing PS-b-PO-b-PS units. The molecular weight of the polymer increased after performing anionic polymerization. Formation of multiblock copolymers leads to less regular phase separation of the PS and PO blocks.
학위논문(석사)--아주대학교 일반대학원 :분자과학기술학과,2017. 2
Keywords: 고분자; 공중합체